Short-Term Rentals and Hotel Accommodation - Almenova, Ariadna; Petrů, Zdenka, 1953-; Feshyna, Olga; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
The diploma thesis deals with the comparison of short-term rentals and hotels, the two segments of hospitality industry. The aim is to evaluate key differences in both segments and economically prove the contribution to the budget. A side goal is to find out Czech’s opinion on short-term rentals. In the theoretical part, the full description of both segments introduced (history, classification, distribution channels, IT solutions, state regulations). Furthermore, the two segments are compared to each other and results of the questionnaire survey interpreted. Based on which, Prague residents are rather supportive towards short-term rentals and according to economic impact short term rentals contribute on a lower rate to the service sector than hotels in Czech Republic. The research can be used as a reference for a hotelier to understand short-term rental segment. For municipal authorities as inspiration to consider imposing legal laws to regulate the segment by issuing licensing instead of entirely prohibiting short-term rentals.
Vedoucí práce: Zdenka Petrů
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: cestovní ruch [obor dipl. práce]; diplomové práce; master's theses